Frequency of Intestinal Parasitism and Epidemiological Characteristics of the 1 to 12 Year-Old Child Population Treated at the Cerro Gordo Type II Urban Outpatient Clinic. Barquisimeto, State of Lara. January-June 2007 - Melisa Fuentes; Liset Galíndez; Dayana García; Nora González; Juan Goyanes; Herrera Eddy; Sánchez Julia (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2011)
A cross-sectional study was conducted to determine intestinal parasitism in children treated at the "Cerro Gordo" Type II Urban Outpatient Clinic in Barquisimeto, Lara. Feces samples were collected from 106 children (1-12 years old) and analyzed using both direct and Ritchie´s technique analyses, demonstrating intestinal parasitism in 42.5% of the children, predominantly of school age (48.9%), but independent of gender. The most frequent agent was Blastocystis hominis (42.2%), followed by Giardia lamblia (37.8%), Entamoeba histolytica/ Entamoeba dispar Complex (13.3%), Hymenolepis nana (11.1%) and Ascaris lumbricoides (4.4%). For children with a normal nutritional condition, 41.7% had parasites, while this value was 35.7% for nutritionally undernourished children. The presence of intestinal parasites showed relations to the community's trash collection management program status (p=0.048). Poor hand washing habits were significantly associated with anal pruritus (p=0.008). Inadequate water quality was related to blastocystosis (p= 0.025) and comensals (p= 0.035). The presence of parasites was not associated with specific gastrointestinal symptoms, socioeconomic status, disposition of excreta, presence of vectors in the home, food washing and storage, frequency of garbage collection, washing of hands, family parasitism history and anti-parasite treatment antecedents.